IMPLEMENTASI METODE EKSPERIMEN DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD/MI - Mardiyah, Chasanatul; Lestari, Dwi Junia (The Elementary Journal, 2024)
Science learning is contextual learning so it is necessary learning media developed. Learning in the current era requires learning systems to be integrated with technology. This research discusses Technology-Based 3-Dimensional Learning Media Innovation in Elementary/MI Science Material. This is done because media development is always ongoing develops to adapt to situations and conditions. The method used by the author is literature study through various documents and references. The results of this research concluded that technology-based 3-dimensional learning media innovation was a breakthrough in overcoming the shortcomings of conventional 3-dimensional media. one of them is through Augmented reality which can be built using the help of applications such as Assemblr Edu. With its attractive advantages and flexible use, this innovation can help increase students' interest and understanding in science learning